Mark Twain and male friendship : the Twichell, Howells and Rogers friendships - Messent, Peter B. (New York ; Oxford : Oxford University Press, 2009)
Combining biography, literary history, and gender studies, this book examines three profoundly influential and vastly different friendships in the life of Mark Twain.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Twain, Mark, -- 1835-1910 -- Friends and associates; Twichell, Joseph Hopkins, -- 1838-1918 -- Friends and associates; Howells, William Dean, -- 1837-1920 -- Friends and associates; Rogers, Henry Huttleston, -- 1840-1909 -- Friends and associates; Authors, American -- 19th century -- Biography; Male friendship -- United States -- History